2020
DOI: 10.1111/ases.12847
|View full text |Cite
|
Sign up to set email alerts
|

Total endoscopic thyroidectomy after open neck biopsy of the follicular lymphoma of the thyroid gland

Abstract: Remote‐access total endoscopic thyroidectomy (TET) is a recently established approach that can avoid producing scars in the neck. There are no clear surgical indications for TET for benign nodules or for malignant tumors at present. We report a successful TET in a 50‐year‐old Japanese woman with follicular lymphoma of the thyroid gland after an open neck biopsy. She had been referred to us with a neck tumor noted 2 months earlier. Because of adhesion, we performed a combined resection of the thyroid and partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It can thus be concluded that if the effects of a previous surgery did not reach the recurrent laryngeal nerve, the risk of complications due to reoperation is low, and in the present case the risk of RLNP was also considered to be low. Several cases in which RAT was performed after an ipsilateral thyroidectomy were recently reported (5,9,10), and in all of these reports, the RATs were safely performed without any complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can thus be concluded that if the effects of a previous surgery did not reach the recurrent laryngeal nerve, the risk of complications due to reoperation is low, and in the present case the risk of RLNP was also considered to be low. Several cases in which RAT was performed after an ipsilateral thyroidectomy were recently reported (5,9,10), and in all of these reports, the RATs were safely performed without any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation is considered to cause fibrosis of soft tissue, leading to high-risk surgery (11). However, several studies of open neck surgery after ipsilateral irradiation demonstrated that the surgery was safely performed, and the complication rates were sufficiently low: 0-1.5% for RLNP, 0-2.8% for hypoparathyroidism, and 0-1.5% for postoperative hematoma (5,(12)(13)(14). Kikuchi et al reviewed 171 cases and reported that there was no significant difference in the incidence of complications between the group of patients with an irradiation history and the non-irradiation history group (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 In addition, a RAT for a patient with a history of ipsilateral neck surgery was described. 66 We have also performed a RAT for a patient with a history of ipsilateral neck irradiation. 67 In that case, the patient had an ipsilateral retroauricular incision and had undergone ipsilateral neck irradiation for the treatment of parotid cancer.…”
Section: Relative Contraindications For a Rapmentioning
confidence: 99%
“…For the transoral approach, a completion thyroidectomy was reported 65 . In addition, a RAT for a patient with a history of ipsilateral neck surgery was described 66 . We have also performed a RAT for a patient with a history of ipsilateral neck irradiation 67 .…”
Section: Applications Of Rapmentioning
confidence: 99%